The Sanitary Pad Waste Management System in the UK - a Problematization Approach - Estrada, Ivanova (2017)
The purpose of the research reported in this paper aims to understand how sanitary waste is managed in the United Kingdom and what drivers led the country to implemented such a system, a problematization approach was followed to formulate the research questions. Inductive thematic analysis was used to process data collected through in depth interviews and secondary data such as governmental documents. The results of the analysis were the two main themes that help the author to present the results: Sanitary Pads’ Commercial Waste Management System and Sanitary Pad Waste Management System initial and current drivers. Finally, the paper discuses how legislation has kept control over how the waste is transported, stored, processed or treated and disposed, presenting the three drives that lead the country to implement a system for sanitary pad waste and two main reasons why the system has not been implemented successfully were identified and presented.